2011
DOI: 10.1111/j.1365-2443.2011.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive effects of arachidonic acid and docosahexaenoic acid on neural stem /progenitor cells

Abstract: Arachidonic acid (ARA) and docosahexaenoic acid (DHA), which are the dominant polyunsaturated fatty acids in the brain, have crucial roles in brain development and function. Recent studies have shown that ARA and DHA promote postnatal neurogenesis. However, the direct effects of ARA on neural stem ⁄ progenitor cells (NSPCs) and the effects of ARA and DHA on NSPCs at the neurogenic and subsequent gliogenic stages are still unknown. Here, we analyzed the effects of ARA and DHA on neurogenesis, specifically maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 43 publications
4
28
2
Order By: Relevance
“…Furthermore, the initial reports of cell viability assays showed cells were most viable when DHA was added at the lowest dose (0.1 µM) (Katakura et al, 2009). There are also differences in methodologies used, as in these other studies the fatty acids were dissolved in media containing 1.0% fattyacid free bovine serum albumin (Katakura et al, 2009;Kawakita et al, 2006), whereas in the present study DHA was dissolved in ethanol and then diluted into the media.. DHA inhibited NSC proliferation consistent with previous studies Katakura et al, 2009); however, others have reported DHA enhances NSC proliferation (Sakayori et al, 2011). Sakoyori and co-workers suggested that the difference in effects on proliferation was the due to the lower DHA concentration promoting the maintenance of gliogenic NSCs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, the initial reports of cell viability assays showed cells were most viable when DHA was added at the lowest dose (0.1 µM) (Katakura et al, 2009). There are also differences in methodologies used, as in these other studies the fatty acids were dissolved in media containing 1.0% fattyacid free bovine serum albumin (Katakura et al, 2009;Kawakita et al, 2006), whereas in the present study DHA was dissolved in ethanol and then diluted into the media.. DHA inhibited NSC proliferation consistent with previous studies Katakura et al, 2009); however, others have reported DHA enhances NSC proliferation (Sakayori et al, 2011). Sakoyori and co-workers suggested that the difference in effects on proliferation was the due to the lower DHA concentration promoting the maintenance of gliogenic NSCs.…”
Section: Discussionsupporting
confidence: 80%
“…Since this was the same dose as was used in our study it is more likely that this discrepancy is due to differences in the experimental conditions. In our study we collected NSC from ED16 fetal mice cortices, whereas Sakayori and co-workers used ED16.5 rats and Katakura and co-workers used ED 14.5 rats (Sakayori et al, 2011). There were also differences in the concentrations of heparin, FGF and EGF between studies, all of which are crucial determinants of NSC fate (Kelly et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo study using juvenile rats, ARA increases proliferation of NSPCs in the hippocampus (Maekawa et al, 2009). In vitro neurosphere assays using cultured NSPCs derived from the embryonic rat cortical primordium, both DHA and ARA added into medium can induce increase in the number of neurospheres at the neurogenic stage (Sakayori et al, 2011). In the gliogenic stage when the neurospheres are passaged, DHA induces neuronal differentiation, whereas ARA causes astrocytic differentiation (Sakayori et al, 2011).…”
Section: Fig 4 Summary Of Relationship Between Output From the Hippmentioning
confidence: 98%
“…In vitro neurosphere assays using cultured NSPCs derived from the embryonic rat cortical primordium, both DHA and ARA added into medium can induce increase in the number of neurospheres at the neurogenic stage (Sakayori et al, 2011). In the gliogenic stage when the neurospheres are passaged, DHA induces neuronal differentiation, whereas ARA causes astrocytic differentiation (Sakayori et al, 2011). It would be interesting to know in future how Fabps are related with these differential roles of DHA and ARA in neurogenesis.…”
Section: Fig 4 Summary Of Relationship Between Output From the Hippmentioning
confidence: 98%